2018
DOI: 10.1097/md.0000000000010818
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative manipulative reduction with Chinese herbs for the treatment of a displaced olecranon fracture

Abstract: Nonoperative manipulative reduction performed by a well-trained physician with Chinese herbs may be a treatment option for displaced olecranon fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Due to delayed healing, patient was offered surgical intervention which may by itself cause nonunion [1] as well as nerve injury [6]. Patient however opted for TCM which has been reported to speed up the healing of humerus [3] and olecranon [4] fractures. In vitro experiment [7] as well in vivo work using rodent models [8] have shown that Chinese medicine have a role to play in speeding up bone healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to delayed healing, patient was offered surgical intervention which may by itself cause nonunion [1] as well as nerve injury [6]. Patient however opted for TCM which has been reported to speed up the healing of humerus [3] and olecranon [4] fractures. In vitro experiment [7] as well in vivo work using rodent models [8] have shown that Chinese medicine have a role to play in speeding up bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…However, TCM specifically for fracture management is rare. Very few cases reported of such use are available in the literature and mostly are from China [3,4]. We report a case of successful healing of midshaft humerus fracture using traditional Chinese medicine.…”
Section: Introductionmentioning
confidence: 98%
“…Non-surgical treatment mainly relies on the close reduction, which is minimal in terms of damage to the human body. 1 However, there are also some disadvantages, such as high requirement for doctors' experience and postoperative complications. Relatively, intramedullary nail fixation is the basic surgical method for long bone fracture treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there are two clinical treatment methods: surgical treatment and non‐surgical treatment. Non‐surgical treatment mainly relies on the close reduction, which is minimal in terms of damage to the human body 1 . However, there are also some disadvantages, such as high requirement for doctors' experience and postoperative complications.…”
Section: Introductionmentioning
confidence: 99%